Using resurvey data to predict changes in ecosystem functioning across protected and unprotected coastal dunes - Greta La Bella; Alicia T. R. Acosta; Tommaso Jucker; Manuele Bazzichetto; Marco Andrello; Marta Gaia Sperandii; Marta Carboni (Conservation Biology, 2026)
Protected areas are generally designed to conserve biodiversity. However, how much they also contribute to maintaining ecosystem functions that plant diversity supports has rarely been tested explicitly, often because of the lack of historical ecosystem function data. We used a trait‐based approach to reconstruct past ecosystem functioning and examine its change over the last 15 years in protected and unprotected coastal dune ecosystems. We resurveyed vegetation in quasipermanent plots and measured several ecosystem functions related to biomass production, carbon, water, nutrient cycling, erosion control, and invasion resistance across six coastal dune sites in central Italy. We used these data to quantify biodiversity–ecosystem function (BEF) relationships. We then used these relationships to hindcast past ecosystem functions based on historical vegetation surveys. Finally, as a case study, we applied this method to assess temporal changes in ecosystem functioning under three protection regimes: national protected areas (i.e., strict protection), Natura 2000 sites (loose protection), and unprotected areas. Biomass production, carbon, and water regulation increased over time in unprotected areas, likely due to an expansion of ruderal and non‐native species, which are usually more productive. In Natura 2000 sites, communities showed a decrease in erosion control and invasion resistance associated with the loss of important dune‐building species and the spread of non‐native species. Only in national protected areas did ecosystem functions not undergo significant temporal changes, and invasion resistance even increased. Our results suggested that ecosystem functioning remained stable over time only in areas under strict protection. More broadly, our results demonstrate the potential for using resurvey data in combination with locally estimated BEF relationships to hindcast past ecosystem functioning. Such an approach can be valuable for monitoring long‐term functional changes in response to conservation.